Factors Structuring the Fish Community in the Area of the Coaracy Nunes Hydroelectric Reservoir in Amapá, Northern Brazil. (March 2016) - Sá-Oliveira, Júlio C.; Isaac, Victoria J.; Araújo, Andrea Soares; Ferrari, Stephen F.
The objective of this study was to document the structure of the fish assemblages found in the aquatic environments affected by the Coaracy Nunes hydroelectric reservoir in Ferreira-Gomes, Amapá (Brazil) and the principal factors that determine this structure. In order to do this, standardized samples were collected of the fauna and the environmental parameters in the four principal sectors of the reservoir (upstream, the reservoir, the lake, and downstream). Fish species richness, abundance, and biomass were estimated for each sector. The abundance data were analyzed using null models of co-occurrence. A multivariate BIO-ENV analysis was used to examine the relationship between biological and environmental factors. The relationship between species richness and biomass of both prey and predator species was analyzed to determine whether predation was affecting community structure. Size spectrum analysis was conducted to verify whether fishing has influenced community structure. The results indicated contrasting seasonal patterns of deterministic processes in the downstream and lake sectors, suggesting that competition or abiotic factors may play a role in community structure. Stochastic patterns were recorded in the other sectors. Environmental factors, such as water transparency and depth, and the reservoir level were also closely related to the relative abundance of species in the communities. The relationship between the species richness and the biomass of predators and prey indicated that predation was an important determinant of community structure, which was interrupted by selective fishing. Despite the stochastic nature of most processes, deterministic factors were fundamental to the structure of the assemblages found in the downstream and lake sectors.